Globalisation, agriculture and development perspectives from the Asia-Pacific - Tonts, Matthew; Siddique, Muhammed Abu B.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2011)
This book explores the links between globalization, agriculture and development in a number of contemporary Asia-Pacific nations. It highlights the complex and diversified nature of agricultural change in these contexts, and the ways in which this shapes patterns of economic and social development. Globalisation, Agriculture and Development shows that while agriculture continues to play an important role in local, regional and national development, both the industry and the communities it supports are facing an increasing number of economic, social and environmental challenges.
Globalisation, agriculture and development : perspectives from the Asia-Pacific / Matthew Tonts and M.A.B. Siddique -- Australian agriculture in the global economic mosaic / Neil Argent -- Market efficiency, agriculture and prosperity in rural Australia / Bill Pritchard and Matthew Tonts -- Globalisation, agriculture and development : New Zealand's path to prosperity? / Kenneth E. Jackson -- Agriculture and economic development in India and China : an overview / M.A.B. Siddique -- Globalisation, India's evolving food economy and trade prospects for Australia and New Zealand / Srikanta Chatterjee, Allan Rae and Ranjan Ray -- Global integration and agricultural productivity in China / Yanrui Wu and Zhao Dingtao -- Globalisation and agriculture in the ASEAN region / M.A.B. Siddique -- Agriculture, development and Southeast Asian megacities / Brian J. Shaw -- Contract farming and technology transfer : perspectives from the Philippines' oil palm industry / Paul Huddleston -- Agriculture, land use and conservation initiatives in Indonesia : implications for development and sustainability / Julian Clifton -- Globalised agriculture, development and the environment / J.N. Callow and Julian Clifton -- Globalisation, agriculture and development in the Asia-Pacific : reflections and future challenges / M.A.B. Siddique and Matthew Tonts.
Includes bibliographical references and index.
Keywords: Globalization -- Asia; Globalization -- Pacific Area; Agriculture -- Asia; Agriculture -- Pacific Area; Asia -- Economic policy; Pacific Area -- Economic policy; Electronic books